Playing to the Positives: Using Synergies to Enhance Kelp Forest Restoration - Eger, Aaron M.; Marzinelli, Ezequiel; Gribben, Paul; Johnson, Craig R.; Layton, Cayne; Steinberg, Peter D.; Wood, Georgina; Silliman, Brian R.; Vergés, Adriana (Frontiers in Marine Science, 2020)
Kelp forests are highly productive foundation species along much of the world’s coastline. As a result, kelp are crucial to the ecological, social, and economic well-being of coastal communities. Yet, due to a combination of acute and chronic stressors, kelp forests are under threat and have declined in many locations worldwide. Active restoration of kelp ecosystems is an emerging field that aims to reverse these declines by mitigating negative stressors and then, if needed, introducing biotic material into the environment. To date, few restoration efforts have incorporated positive species interactions. This gap presents a potential shortcoming for the field as evidence from other marine ecosystems illustrates that the inclusion of positive species interactions can enhance restoration success. Additionally, as the climate continues to warm, this approach will be particularly pertinent as positive interactions can also expand the range of physical conditions under which species can persist. Here we highlight how practitioners can use positive density dependence within and amongst kelp species to increase the chances of restoration success. At higher trophic levels, we emphasize how co-restoring predators can prime ecosystems for restoration. We also investigate how emerging technologies in genetic and microbial selection and manipulation can increase the tolerance of target species to warming and other stressors. Finally, we provide examples of how we can use existing anthropogenic activities to facilitate restoration while performing alternative purposes. As kelp forests continue to decline and the field of kelp restoration continues to develop, it is also important that we monitor these potential advancements and ensure they do not have unintended ecosystem effects, particularly with untested techniques such as genetic and microbial manipulations. Nevertheless, incorporating positive species interactions into future restoration practice stands to promote a more holistic form of restoration that also increases the likelihood of success in a shifting seascape.